2005
DOI: 10.1007/s00705-005-0642-6
|View full text |Cite
|
Sign up to set email alerts
|

Human ribosomal protein L18a interacts with hepatitis C virus internal ribosome entry site

Abstract: Translation initiation of hepatitis C virus RNA occurs via ribosome binding to an 'internal ribosome entry site (IRES)' located in the 5'untranslated region of the viral RNA. The principle interaction between the 40S ribosomal subunit and the HCV IRES has been shown to be largely factor independent, which is followed by the joining of the 60S ribosomal subunit to form functional 80S complex. However several additional cellular proteins have been reported to bind to HCV IRES and enhance the initiation of transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Consistent with its role in RNA trafficking, p30 nuclear/nucleolar retention is partially dependent on de novo mRNA transcription. We also report that p30 interacts with a nucleolar constituent of the large ribosomal subunit L18a, a protein shown previously (12,(32)(33)(34) to modulate internal initiation of translation. * This work was supported by NIAID Grant AI058944 from the National Insti-…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…Consistent with its role in RNA trafficking, p30 nuclear/nucleolar retention is partially dependent on de novo mRNA transcription. We also report that p30 interacts with a nucleolar constituent of the large ribosomal subunit L18a, a protein shown previously (12,(32)(33)(34) to modulate internal initiation of translation. * This work was supported by NIAID Grant AI058944 from the National Insti-…”
mentioning
confidence: 53%
“…Several studies have shown that the ribosomal protein L18a interacts with viral protein and eukaryotic initiation factor-3 and facilitates internal re-initiation of translation in cytomegalovirus and hepatitis C virus (12,(32)(33)(34). Our results indicate that this phenomenon is conserved in HTLV-I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been described that the three ribosomal proteins have extraribosomal functions. For example, RPL18 plays an important role in translation of some viruses such as the cauliflower mosaic virus (Leh et al, 2000), while the RPL18A protein interacts with the internal ribosomal entry site (IRES) of Hepatitis C virus (Dhar et al, 2006), a member of the Flavivididae family. Additionally, the RPL7 has been involved in the anchoring of the ribosome to the endoplasmic reticulum membranes (Wu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian homolog of Rpl20A is the ribosome protein L18a. It has been suggested that L18a may interact with RNA and promote translation (20). Rsm22 also has a mammalian homolog, suggesting that it is important for the function of the mitochondrial ribosome (96).…”
Section: Discussionmentioning
confidence: 99%